2010
DOI: 10.1089/mdr.2009.0127
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antimicrobial Resistance ofSalmonellaSerotypes in Chickens from Retail Markets in Yaounde (Cameroon)

Abstract: From February 2006 to January 2007, 150 chickens were collected from eight retail markets in Yaounde, and 90 (60%) tested positive for Salmonella. Seventy-nine chickens were contaminated with only one Salmonella serotype, 10 with two different serotypes, and 1 with four serotypes. The most prevalent serotypes were Enteritidis (47 strains) and Hadar (29 strains). The isolates were tested for their susceptibilities to amoxicillin, amoxicillin/clavulanic acid, cefoxitin, cefotaxime, gentamicin, streptomycin, tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
4
11
0
Order By: Relevance
“…This result was supported by Jahan et al (2013) and Khan et al (2005) where isolates were sensitive to ciprofloxacin and chloramphenicol. The result is also consistent with Wouafo et al (2010). The isolates were resistant to erythromycin, and amoxycillin which is similar to report of Hyeon et al (2011) and Khan et al (2005).…”
Section: Coli (N=4)supporting
confidence: 91%
“…This result was supported by Jahan et al (2013) and Khan et al (2005) where isolates were sensitive to ciprofloxacin and chloramphenicol. The result is also consistent with Wouafo et al (2010). The isolates were resistant to erythromycin, and amoxycillin which is similar to report of Hyeon et al (2011) and Khan et al (2005).…”
Section: Coli (N=4)supporting
confidence: 91%
“…In this study, 8 different antibiotics available in the market were used to study antibiogram profiles of the E. coli and Salmonella spp. isolated from diarrhoeic cattle by disc diffusion method and the results were supported by Akond et al, 2009;Wouafo et al, 2010;Hyeon et al, 2011;De et al, 2012;Jeyasanta et al, 2012;Jahan et al, 2013. Due to financial crisis and limited time following further studies like collection of more samples covering many areas and farms of Bangladesh to get more precise information, molecular detection of shiga toxin producing E. coli, molecular characterization of the isolated bacterial species by pulsed field gel electrophoresis (PFGE), 16S rRNA gene sequencing of the isolated E. coli and Salmonella spp., serotyping, multiplex PCR of the isolated Salmonella spp., pathogenicity study would not be possible.…”
Section: Discussionsupporting
confidence: 53%
“…Previous studies have reported high level of resistance to tetracycline in Cameroon. Salmonella sp isolated from chicken in the market showed 84.5% resistance to tetracycline [29] while lowest resistance rate of bacteria isolates from farm wastes to tetracycline of > 50% [30] have been reported. Guetiwa [28] also indicated that out of eleven different bacteria isolated from poultry farm in Cameroon, they were shows overall 63.6% resistance to oxytetracycline.…”
Section: Discussionmentioning
confidence: 99%